Structural study of composites of aerosil fumed silica and tetraethoxysilane-derived sonogels - Donatti, D. A.; Ruiz, A. I.; Vollet, D. R. (Elsevier B.V., 2005)
Composites of aerosil fumed silica and tetraethoxysilane-derived sonogel were prepared by changing the aerosil content between 0 and 30wt% with respect to the silica content in the original tetraethoxysilane (TEOS). The structural characteristics were studied by density and Vickers microhardness measurements and analyzed by means of small-angle X-ray scattering (SAXS). The structure of the composite aerosil/TEOS-derived sonogel can be described as inclusions of the aerosil particles embedded in the matrix of the TEOS-derived sonogel, forming an aerosil/matrix interfacial surface inside the composite. The weakening of the bonding of aerosil/matrix interface, as suggested by the reported decrease in microhardness, increases the fracture toughness of the composite. The additive effect of the aerosil particles on the structure of the sonogel accounts for the increase of the bulk density and reduction of the specific surface of the composite. Some internal structure associated with the microclusters making up the sonogels is apparent from systematic deviations from Porod's law found in the system with small aerosil contents. (c) 2005 Elsevier B.V. All rights reserved.